2017
DOI: 10.1186/s12879-017-2913-8
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the safety of voriconazole in definitive, empirical, and prophylactic therapies for invasive fungal infections

Abstract: BackgroundVoriconazole has been used in the treatment and prophylaxis of invasive fungal infections (IFIs) while its wide use was limited by some frequent adverse events, especially neurotoxicity, hepatotoxicity and even renal disruption. The aim of this study was to comprehensively compare voriconazole-induced toxicity, including tolerability, neurotoxicity, visual toxicity, hepatotoxicity and nephrotoxicity with the composite of other antifungals commonly used in clinic.MethodsBibliography databases were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…The comparatively large number of patients fulfilling the pediatric EBMT criteria indicates a risk of over-diagnosis. There is, for instance, a risk that slight increases in bilirubin may be caused by hepatotoxic side effects of medication frequently used in the clinic, such as antibiotics, antiviral drugs and antifungals (in particular voriconazole [33] and carbapenems [34]). As we are the first to assess these proposed criteria, we have only our own numbers to consider regarding the risk of over-diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The comparatively large number of patients fulfilling the pediatric EBMT criteria indicates a risk of over-diagnosis. There is, for instance, a risk that slight increases in bilirubin may be caused by hepatotoxic side effects of medication frequently used in the clinic, such as antibiotics, antiviral drugs and antifungals (in particular voriconazole [33] and carbapenems [34]). As we are the first to assess these proposed criteria, we have only our own numbers to consider regarding the risk of over-diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of studies has found that the tolerability of voriconazole was slightly inferior, and the risk of neurotoxicity and visual toxicity were higher than those of alternative drugs. Only the risk of nephrotoxicity proved to be lower than that of alternatives [117]. Hence, voriconazole should be used as prophylaxis for LTR at high risk for IA.…”
Section: Antifungal Prophylaxismentioning
confidence: 98%
“…1,2 It is associated with adverse side effects including visual symptoms, neurological disorders and hepatotoxicity. [3][4][5][6][7][8] Xing et al 9 comprehensively compared voriconazole-induced toxicity with other antifungals, and there were significant differences in hepatotoxicity (odds ratio [OR] 1.60), visual symptoms (OR 6.50) and neurotoxicity (OR 1.99). Therapeutic drug monitoring (TDM) is used to guide voriconazole therapy to prevent drug-related adverse events and to improve clinical responses by individualising dose regimens.…”
Section: Introductionmentioning
confidence: 99%